(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Purpose The purpose of writing this book review is to make the readers of leadership get an overview of the classic book from Harvard Business Review (HBR). The book is basically a compilation of ten best articles on leadership from the data bank of HBR. One of the most important features of the book is that all the articles are backed by research. Reading on leadership is required more than ever before in the era of the COVID-19 pandemic, as it has created new challenges and opportunities for the global business environment. This book is a one to be read in this hard time.